(untitled) (Aporte Santiaguino, 2025)
The objective of this study was to determine the relationship between radio link and early warning in the event of a flood in the Palcacocha Lagoon in Huaraz. The methodology was quantitative, with a non-experimental, cross-sectional, and correlational design. The instrument was a questionnaire, administered to 68 residents of the city of Huaraz. The Spearman’s Rho correlation coefficient was 0.595, with a significance level of 0.000, less than 5%. Therefore, the null hypothesis was rejected and the alternative hypothesis accepted. This showed a medium positive relationship between radio link and early warning in the event of a flood. Likewise, a medium positive correlation was found between autonomous radio link and the early warning dimension in the event of a flood according to Spearman’s Rho of 0.628. Finally, a low positive correlation was found between autonomous radio link and the early response dimension in the event of a flood according to Spearman’s Rho of 0.445. To ensure the reliability of the questionnaire, Cronbach’s alpha was applied, obtaining 0.945 for the radio link variable and 0.845 for early warning. It is concluded that a good radio link system will improve early warning for the Palcacocha Lagoon flood in Huaraz. Information and Communication Technologies, through radio link devices that allow long-distance communication. In society, they have revolutionized the way we live, work and communicate, particularly in the city of Huaraz and the snow-capped mountains of the Cordillera Blanca (Palcacocha Lagoon), proposing solutions to natural disasters, implementing an Early Warning System, which allows for sustainable development, facing current and future challenges.